Na politicheskom Olimpe . Na politicheskom Olimpe . On the Political Olympus . На политическом Олимпе - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The attempted coup d'état of August 1991 and the situation two years on. Featured in the program: Shumeiko, Vladimir Filippovich (First Deputy Prime Minister of the Russian Federation); Yeltsin, Boris Nikolayevich (President of the Russian Federation); Kurkova, Bella Alekseevna (Journalist); Gergiev, Vladimir Abisalovich (Art Director of the Mariinsky Theater) Contributors: Kurkova, Bella Alekseevna (Anchor) Августовский путч 1991 года и ситуация 2 года спустя. В программе участвуют: Шумейко, Владимир Филиппович (Первый заместитель председателя Правительства Российской Федерации); Ельцин, Борис Николаевич (Президент Российской Федерации); Куркова, Бэлла Алексеевна (Журналистка); Гергиев, Владимир Абисалович (Художественный руководитель Мариинского театра) Создатели: Куркова, Бэлла Алексеевна (Ведущий/Ведущая)